Impacts of Changbai Mountain Topography on the Extreme Precipitation From Super Typhoon Maysak - Zhu, Dan; Zhi, Xiefei; Wang, Ning; Chen, Changsheng; Tian, Xiao; Yu, Yueming (Frontiers in Environmental Science, 2022)
Based on hourly gridded precipitation data (0.1°) calculated by the China Meteorological Administration (CMA), the European Centre Medium-Range Weather Forecasts (ECMWF) reanalysis data, and microwave measurements, this paper investigated the extreme precipitation induced by the Typhoon Maysak in Northeast China (September 2020), using the Advanced Research dynamic core of the Weather Research and Forecasting Model (WRF-ARW). The study focused on Changbai Mountain topography and the extreme precipitation in Jilin Province. The results show that two extreme precipitation centers corresponded well to the local terrain height in Jilin Province. The Changbai Mountain range, which mainly lies in southeastern Jilin Province, affected the typhoon in three aspects, i.e., blocking drag, forcing uplift, and promoting moisture convergence. Because of the blocking drag of the mountain topography, the duration of severe precipitation was prolonged. The overlap of the area affected by the peripheral cloud band of the typhoon and the direction of the typhoon was largely responsible for the extreme rainfall. The dynamic lifting by the mountainous terrain and the reinforced moisture convergence, also considerably increased precipitation. Microwave measurements show that water vapor density profile increased rapidly to the peak (14 g/m3), and the high moisture density was retained for at least 15 hours in lower layer. The prolonged, continuous, and abundant moisture transport offered a sufficient water vapor supply for this severe precipitation event. According to the estimation of precipitation rate, the increment of torrential rainfall on Changbai Mountain during the severe precipitation period reached 6.8 mm/h, about 41% of the total rainfall in this period. Finally, the topographic sensitivity test indicated that when the terrain of Changbai Mountain was lower, the convergent ascending motion, precipitable water, and storm-relative helicity were weaker, and the rainfall distribution markedly changed. This finding further verifies the importance of the Changbai orography in the extreme precipitation event induced by Typhoon Maysak.